Conformationally restricted goniofufurone mimics with halogen, azido or benzoyloxy groups at the C-7 position: Design, synthesis and antiproliferative activity. Issue 36 (6th September 2018) - Svirčev, Miloš; Benedeković, Goran; Kovačević, Ivana; Popsavin, Mirjana; Kojić, Vesna; Jakimov, Dimitar; Srdić-Rajić, Tatjana; Rodić, Marko V.; Popsavin, Velimir
Abstract: A series of new conformationally restricted goniofufurone mimics, bearing an additional 1, 3-dioxan ring and a halogen, azido or benzoyloxy functionality at the C-7 position has been designed and synthesized. The Appel reaction was used for replacement of 7-OH group with Cl or Br functions in tricyclic lactone (3 ). 7-Iodo derivative (3d ) was prepared by using the Ph3 P/I2 /2, 6-lutidine reagent system. 7-Fluoro group was introduced by treatment of 3 with DAST, while the corresponding 7-azido and 7-benzoyloxy derivatives have been prepared by multistep sequences. Synthesized products were evaluated for their ability to inhibit growth of selected human malignant cell lines. Structure-activity relationships demonstrated that the nature of a substituent at the C-7 position could enhance the antiproliferative activity of the analogues. The preliminary study on the mechanisms indicated that all synthesized compounds induced apoptosis in 61–77% of K562 cells. Graphical abstract: Image 1 Highlights: Novel conformationally restricted goniofufurone mimics have been synthesized. The most of synthesized compounds are cytotoxic toward human tumour cell lines. SAR analysis has pointed to structural features responsible for antitumour activity. The most of analogues induced apoptosis in K562 cells in caspase-dependant way.